Метод измерения амплитудной диаграммы направленности зеркальных параболических антенн в звуковом диапазоне частот - Садченко, А.В.; Кушниренко, О.А.; Альхамиди, М.Т.; Алхади, А.М. (Технология и конструирование в электронной аппаратуре, 2016)
Предложена методика измерения направленных свойств зеркальных параболических антенн в звуковом диапазоне частот с использованием дешевой элементной базы, основанная на методе полигонных измерений. Показана взаимосвязь эквивалентных частот, лежащих в различных диапазонах, и определены требования к минимальным размерам антенны. Вимірювання діаграми спрямованості апертурних антен безпосередньо в мікрохвильовому діапазоні потребує достатньо великих витрат. Водночас, вартість генерувальних та приймальних пристроїв для частот акустичного діапазону є на кілька порядків меншою. В даній роботі запропоновано методику вимірювання спрямованих властивостей дзеркальних параболічних антен в звуковому діапазоні частот з використанням дешевої елементної бази. За основу обрано метод полігонних вимірювань, який не потребує внесення змін до конструкції антени, що досліджується. Показано взаємозв'язок еквівалентних частот, що лежать в різних діапазонах, і визначено вимоги до мінімальних розмірів антени. Directivity pattern (DP) or graphical representation of the dependence of gain factor (directivity gain) of antennas on the direction of the antenna in the target plane is the main characteristic that describes its directional properties. Running DP measurements directly in the microwave range is very expensive. While generating and receiving devices for the acoustic frequency range are reasonably priced. In this paper, we propose a method for measuring the amplitude directivity pattern of parabolic mirrored antennas on the basis of sound equivalent, which is based on the identity of the numerical values of the directivity gain of microwave range, and at audio frequencies. The paper presents analytical expressions for the calculation of equivalent frequency and defines the requirements for the minimum size of the antenna. The paper contains a modified block diagram for an amplitude directivity pattern meter for parabolic mirrored antennas in the audio frequency range.